Effects of auriculotherapy on blood pressure levels in hypertensive adults and older adults - Victor Hugo Martins Santos; Margani Cadore Weis-Maia; Camila Maria Cenzi; Jaqueline Costa Lima; Camila de Souza dos Santos; Marina Nolli Bittencourt (Rev Rene, 2025)
Objective: to evaluate the effect of auriculotherapy on blood pressure and well-being parameters in hypertensive adults and older adults. Methods: a quasi-experimental, before-and-after study of a group undergoing a course of auriculotherapy. The initial sample was 41 people and the final sample was 29. Blood pressure was measured before the intervention, immediately after and five days later. The analysis of variance test was applied to compare the blood pressure means at the three time points. The World Health Organization-Five Well-Being Index questionnaire was used to check well-being. Results: there was a statistically significant difference between the systolic blood pressure levels before and after the intervention (p=0.001), with means of 133.17 mmHg pre-intervention, 127.07 mmHg immediately after care and 127.58 mmHg after five days. The well-being score improved significantly between the pre-intervention and the fifth day (p=0.023). Conclusion: auriculotherapy had beneficial effects on systolic blood pressure levels and the well-being of the population it served, proving to be a collaborative strategy in the management of hypertension. Contributions to practice: auriculotherapy can help regulate blood pressure, promote greater autonomy for nurses and patient-centered care. Brazilian Registry of Clinical Trials: RBR-6r8y39d.